Evaluating the environmental-technology gaps of rice farms in distinct agro-ecological zones of Ghana - Asravor, J.; Wiredu, A.N.; Siddig, Khalid; Onumah, E.E. (MDPI, 2019)
Rice (Oryza sativa) is an important food staple and a cash crop, which is cultivated in all the ten regions of Ghana under varying agro-ecological conditions. These conditions also reflect the production technologies used and the total farm output. In an attempt to determine the potential sources of production shortfalls on rice farms in Ghana, this paper estimates the production efficiency and the environmental-technology gaps of rice-producing households in the forest-savannah transition and guinea savannah agro-ecological zones of Ghana. The paper adopts the stochastic metafrontier framework, which permits technology-related inefficiency effects to be extricated from managerial inefficiency effects for appropriate policy formulation. In contrast to past studies, the empirical findings reveal that farms in the two agro-ecological zones adopt heterogeneous production technologies due to differences in their production environments. This is indicated by the estimated mean environmental-technology gap ratios of 0.95 and 0.50, and mean metafrontier technical efficiencies of 0.56 and 0.42 for farms in the forest-savannah transition and guinea savannah zones, respectively. These findings call for agricultural policy formulation in Ghana to be targeted at the prevailing environmental conditions of the various agro-ecological zones rather than being all-inclusive in addressing the extant inefficiencies in the rice production systems of Ghana.